"Comportamiento agronómico y rendimiento del cultivo de arroz (Oryza sativa L.), mediante la aplicación de ácidos húmicos en suelos salinos, en la zona de Yaguachi - Ponce De La Cruz, Ismael Alejandro (2019)
VIII. SUMMARY The present experimental work was established in lands of the Yaguachi area, between the geographic coordinates of 221196.53 UTM of South latitude and 277539.36 UTM of West longitude, with a height of 15 m.s.n.m. The zone presents a humid tropical climate, with an average temperature of 25.0 ° C; an annual rainfall of 2298.8 mm, humidity 82% and 998.2 hours of annual average heliophany. Seeds of rice, variety Iniap FL 1480 Cristalino were used as seed material. The treatments consisted of Black gold, in a dose of 20.0 kg / ha; Huminrich 15.0 kg / ha; Huma K 15.0 kg / ha; Robusterra 15.0 kg / ha and a Control (Without application). The experimental design of complete blocks was used at random, with five treatments and four repetitions. The variables to be evaluated were subjected to the analysis of variance, using the Tukey significance test at 95% probability for comparisons of treatment means. All the necessary agricultural work was carried out in the cultivation of rice for its normal development, such as land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. To estimate the effects of the treatments, data were taken on plant height, number of tillers and panicles, days of flowering and harvest, length of panicles, grains per panicles, weight of 1000 grains, grain yield and economic analysis. . For the results obtained, it was determined that a favorable response was presented in the agronomic behavior and yield of the rice crop with the application of humic acids; the treatments that did not apply humic acids influenced so that variety of rice flourishes and it is harvested in smaller time; plant height, number of tillers and panicles / m2, panicle length, grains per panicles and weight of 1000 grains obtained higher results when Huminrich was used with a dosage of 15.0 Kg / ha and with the use of Huminrich with doses of 15.0 Kg / ha showed a higher crop yield of 4534.0 kg / ha and a higher net profit of $ 139,76.